Respuestas
Respuesta dada por:
1
Respuesta:
Explicación paso a paso:
1)
a. (-2) + (-3)= -2 - 3 = -5
b. 4 + (-12) = 4 - 12 = -8
c. (-3) + 8 = 5
d. (-2) + 5 = 3
e. 7 +(-7) = 7 - 7 = 0
f. 0 +(-3) = 0 - 3 = -3
2)
a. 8 + x = 12 ⇒ x= 4
b. x +(-2) = -5 ⇒ x - 2 = -5 ⇒ x= -3
c. (-4) + x = 10
d. (-2) + x = 0
e. x + 6 = -4 ⇒ x = -10
f. 1 + x = -12 ⇒ x = -13
3)
y esta te mando una imagen ;3 ten buen dia y suerte
Adjuntos:
![](https://es-static.z-dn.net/files/d73/afe76e0f10e433dbaf738b35da4e27a1.jpg)
Preguntas similares
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 8 años